Saint Lucia. Significant achievements 2014 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamerica de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in St. Lucia during 2014 are identified, with respect to the needs and interests of the country, strengthening on topics such as sustainability, exports, trade, irrigation, labeling, finance, aquaculture, forest resource management, business , inclusion of women and in the value chains of goats, sheep and pineapple.